Prototipe Pengaman Kebakaran Rumah Menggunakan Thermal Camera - Saputra, Filmada Ocky; Harisa, Ardiawan Bagus; Arifin, Zaenal (Elektrika, 2021)
80% of cases of building or house fires in Indonesia are caused by electrical short circuits. Currently, there are only MCB and ELCB devices protecting for building electrical installations, but these devices cannot protect the conditions that cause fires. In a short circuit, there will be heating of the short cable or device. In this study, researchers used a thermal camera that can be placed on an electrical panel to be able monitor the temperature of electrical panel which includes cables, MCB, or can be placed on other devices. When the detected object temperature exceeds a predetermined limit, the device will provide a warning in the form of sound and text and can automatically cut off electricity in the building’s electricity network. This research produces a prototype of a power grid safety device using a Raspberry Pi that can be applied to buildings and objects that have the potential to emit excess heat that can cause fires. Systems it will be able to monitor, provide warnings and can automatically cut off the electricity network when the temperature of the observed object exceeds the specified limit and has the potential to emit excess heat which can cause a fire.